NURSES' ROLE IN THE IMPROVEMENT OF DIABETES MELLITUS PATIENTS' QUALITY OF LIFE - Rodrigues, Josilene Araujo; Lima, Francimara de Jesus Sousa; Santos, Ariane Gomes dos (Journal of Health Care, 2015)
Objective: To analyze the conditions that affect the quality of life of patients with diabetes mellitus accordingto their limitations. Materials and Methods: This is an integrative literature review, data collectioncarried out from February to August 2014. We used the descriptors "quality of life", "diabetesmellitus"and "nursing". The final sample consisted of 7 (seven) items belonging to the databases LILACS,MEDLINE and BENDENF with time frame between 2009 to 2014. The analysis and discussion of thedata proceeded descriptively. Results: The contents of the selected articles were grouped into three analyticalcategories: "factors and aspects associated with diabetes that affect quality of life","compliance tothe treatment" and "nursing knowledge about actions developed in care of diabetic patients". The studyshowed that many people with diabetes are unaware about the chronicity and the numerous situationsimposed by the disease, there are adhesion problems for elements that are part of therapy: drug treatment,exercise and eating plan. Studies also showed that nurses have interpersonal skills, knowledge, skill andability to interact with the patient, accepting their problems, beliefs and desires. Final thoughts: To meetexpectations with respect to treatment, disease control and a decent quality of life for people with diabetes,nurses have the mission to develop strategies to convince the patients to adhere to treatment, change theirlife style, make them aware of the disease, and develop self-care.
Keywords: Quality of life; diabetes mellitus; nursing.